Em busca da excelência no desporto adaptado: um estudo de caso - Celestino, Tadeu (2021)
The adapted sport has gradually to take its place in cultural sports practices of society. Underlying this recognition are the achievement of excellence systematically perpetuated by disabled athletes at major sporting events such as the Paralympic Games, granting them social recognition and inclusion. However, the understanding of excellence in this context is still very incipient. Thus, the objective of this study was to identify the factors that underlie the excellence in the adapted sport, starting from the analysis of the life course of Mário Trindade Paralympic athlete. This study was developed under the paradigm of the "Life Stories" methodology. Data were collected through a semi-structured interview. We used the technique of content analysis with the software Nvivo 11. Thus, results analysis allows us to conclude that the excellence of this athlete is based on a set of factors, which by their primary action in the performance of excellence, are associated with deliberate practice, diversification of practice, free practice and psychological factors On the other hand, by its secondary modeling action in the performance of excellence, we identify the socio-cultural constraints and the significant people as important modelers of excellence.